Lessons Learned: Forty Years of Clinical Work With Suicide Loss Survivors - Jordan, John R. (Frontiers in Psychology, 2020)
The author has been a grief therapist in private practice for almost 40 years. The largest percentage of his clients have been suicide loss survivors, and in this article, the author reflects on the “lessons learned” about how grief therapy with survivors is both the same as, and very different from, work with clients bereaved after other types of losses. After briefly reviewing some of the empirical literature about differences between suicide bereavement and grief after other modes of death, the author argues that perhaps the most distinguishing and difficult aspect of a suicide loss is the “perceived intentionality” of the death, and the related “perceived responsibility” for the death. The author goes on to identify a number of tasks of psychological reintegration after a suicide loss that can serve as a template for treatment goals for clinicians and clients alike. These include the cultivation of a very specific type of “nurturing” therapeutic alliance; extensive psychoeducation about suicide, trauma, and grief; the need to help the client repair the psychological continuing bond with the deceased; and providing gentle support for the survivor in rebuilding an assumptive world that has been shattered by the suicide of a loved one. Finally, the article concludes with a discussion of the clinical implications of these differences for work with suicide loss survivors.